2022
DOI: 10.1155/2022/5989889
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Isothermal Signal Amplification Technique in the Etiological Diagnosis of Gonorrhea and Drug Resistance Gene Detection

Abstract: Background: Isothermal signal amplification technique is developed based on the rolling ring amplification mechanism of cyclic DNA molecules in nature. This technique plays an extremely beneficial role in gonorrhea pathogen identification and drug resistance gene detection. Aims: This study analyzes the isothermal signal amplification techniques in the etiological diagnosis of gonorrhea and drug resistance gene detection. Materials and Methods: Urethral, cervical secretion, or prostatic fluid samples from 322 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%